The effect of using the constructivist learning model on learning some skills of the handles horse apparatus - Hassoon Mashkoor, Shaymaa; Ammar Lifta, Iqbal (International Journal of Psychosocial Rehabilitation, 2020)
Gymnastics is one of the games whose performance depends on mastering motor skills on the six devices (a horse with handles), Which requires an acceptable level of physical and skill preparation using the best methods of learning to reach the goal in the fastest time and least effort. Learning and mastering it leads to improved performance and ease of use on other devices. This method is one of the educational methods that assume that in order for students to achieve the greatest possible benefit from their education, they must not be allowed to be only passive recipients, but rather as productive individuals in their groups by urging them to actively participate in learning, to interact with their colleagues and explain to them what they have learned, and to listen for points of view. their gaze and encourage each other. In light of the findings of the two researchers, the following was concluded: 1- The clear effect of the constructivist learning model on learning and retaining the skill of the handles device. The researchers also recommend Bailey 1- Adopting the constructivist educational model according to the constructivist theory in teaching other basic skills effectively gymnastics 2- Providing the appropriate educational climate for the development of creative thinking and other types of thinking in our classrooms by developing the spirit of cooperation and respect for the other opinion, encouraging research and exploration and providing the necessary financial capabilities for that.